Identification of quorum sensing‐controlled genes in Burkholderia ambifaria. Issue 2 (5th February 2013) - Chapalain, Annelise; Vial, Ludovic; Laprade, Natacha; Dekimpe, Valérie; Perreault, Jonathan; Déziel, Eric
Abstract: The Burkholderia cepacia complex (Bcc) comprises strains with a virulence potential toward immunocompromised patients as well as plant growth–promoting rhizobacteria (PGPR). Owing to the link between quorum sensing (QS) and virulence, most studies among Bcc species have been directed toward QS of pathogenic bacteria. We have investigated the QS of B. ambifaria, a PGPR only infrequently recovered from patients. The cepI gene, responsible for the synthesis of the main signaling molecule N ‐octanoylhomoserine lactone (C8 ‐HSL), was inactivated. Phenotypes of the B . ambifaria cepI mutant we observed, such as increased production of siderophores and decreased proteolytic and antifungal activities, are in agreement with those of other Bcc cepI mutants. The cepI mutant was then used as background strain for a whole‐genome transposon‐insertion mutagenesis strategy, allowing the identification of 20 QS‐controlled genes, corresponding to 17 loci. The main functions identified are linked to antifungal and antimicrobial properties, as we have identified QS‐controlled genes implicated in the production of pyrrolnitrin, burkholdines (occidiofungin‐like molecules), and enacyloxins. This study provides insights in the QS‐regulated functions of a PGPR, which could lead to beneficial potential biotechnological applications. Abstract : Burkholderia ambifaria is a growth‐promoting rhizobacteria that belongs to the B. cepacia complex (Bcc), also known for its virulence potential toward immunocompromised patients. To better understand the QS circuitry in this bacterium, a whole‐genome transposon‐insertion mutagenesis strategy has been performed. Among the QS‐controlled genes identified in the study, several are implicated in antifungal and antimicrobial properties, which could lead to attractive biotechnological applications.